PENGEMBANGAN TES FORMATIF DAN SUMATIF PADA MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Anggrayni, M.; Saputra, Riyadi; Yulita, Yulita (Universitas Negeri Medan, 2023)
This research has the following objectives: (1) to develop formative and summative tests in grade IV elementary school science subjects; (2) improve evaluation activities in grade IV elementary school science subjects that have not been maximized, especially in formative and summative tests; (3) validate the feasibility of formative and summative test products; (4) validate the practicality of formative and summative test products. The type of research used Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques are obtained from observations, interviews, test questionnaires and documentation. Quantitative data analysis of validity and practicality trial results. The progress of student learning outcomes in grade IV elementary school science learning has increased significantly compared to before formative and summative tests were developed. This is evidenced from the results of the educator response questionnaire sheet obtained an average value of 92.71% and student responses obtained an average value of 88.54% in the very practical category.